The future of the French trade unions - Dominique Andolfatto; Dominique Labbé (Management Revue, 2012)
This article investigates the transformations of the French unionism and of the French system of industrial relations over the last years and their probable future. It shows: an evolution from a militant unionism to a professionalized trade unionist system; the decline of collective actions; the increase of negotiation, especially at plant level; the dependence of unionists on their employers for their funding, their resources and their careers. This evolution marks a shift towards a new system which is very different from a 'unionist Latin model' depicted in traditional literature on French unionism.
Keywords: J50; J51; J52; 650; France; trade unions; de-unionization; strikes; collective bargaining; union budgets